2008
DOI: 10.1007/s12033-008-9106-z
|View full text |Cite
|
Sign up to set email alerts
|

Allene Oxide Cyclase from Camptotheca acuminata Improves Tolerance Against Low Temperature and Salt Stress in Tobacco and Bacteria

Abstract: Allene oxide cyclase (AOC, E 5.3.99.6) is an essential enzyme in jasmonate (JA) biosynthetic pathway. An AOC gene (defined as CaAOC, Database Accession No. AY863428) had been isolated from Camptotheca acuminata in previous work. Real-time quantitative PCR analysis indicated that mRNA expression of CaAOC was induced by salt stress (120 mM NaCl) and low temperature (4 degrees C). In order to further investigate the role of AOC gene in the processes, CaAOC was introduced into tobacco via Agrobacterium tumefaciens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…SAHA treatment enhanced MeAOC4 expression to 32.8-fold compared with untreated plants (Figure 7A). Previous studies have revealed that overexpression of AOCs can confer salinity stress tolerance to several crops (Yamada et al, 2002; Pi et al, 2009; Zhao et al, 2014). According to the current cassava genome database, AOCs constitute a small gene family ( MeAOC3-1 : RknMes02_049533: cassava4.1_014582m; MeAOC3-2 : RknMes02_054684: cassava4.1_026961m; and MeAOC4 : RknMes02_051874: cassava4.1_022180m) in cassava (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…SAHA treatment enhanced MeAOC4 expression to 32.8-fold compared with untreated plants (Figure 7A). Previous studies have revealed that overexpression of AOCs can confer salinity stress tolerance to several crops (Yamada et al, 2002; Pi et al, 2009; Zhao et al, 2014). According to the current cassava genome database, AOCs constitute a small gene family ( MeAOC3-1 : RknMes02_049533: cassava4.1_014582m; MeAOC3-2 : RknMes02_054684: cassava4.1_026961m; and MeAOC4 : RknMes02_051874: cassava4.1_022180m) in cassava (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…[See online article for color version of this figure. ] sexangula) or a Camptotheca acuminate AOC in tobacco (Nicotiana tabacum) cells (Yamada et al, 2002;Pi et al, 2009). It is also well established that exposure to JA can improve the salinity tolerance of a number of plant species (Walia et al, 2007;del Amor and CuadraCrespo, 2011;Ismail et al, 2012).…”
Section: The Elevation Of Ja Synthesis Branch Enhances Salinity Tolermentioning
confidence: 99%
“…AOC genes have been cloned from several plant species, including tomato [7], mangrove [8], Arabidopsis thaliana [9], barley [10], barrel medic [11], Hyoscyamus niger [12], Camptotheca acuminate [13], Jatropha curcas [14], Physcomitrella patens [15], Glycine max [6], and Leymus mollis [16]. Characterization of these genes from different plants has provided valuable information about their biochemical and physiological roles in adaptation to a variety of biotic and abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of JcAOC in Escherichia coli conferred resistance to salt stress and low temperature [14]. Ectopic overexpression of an AOC gene cloned from C. acuminate using the viral 35S promoter improved tolerance against salt stress and low temperature in transgenic tobacco plants compared to wild-type controls [13]. GmAOC5 transgenic tobaccos showed enhanced tolerance to oxidative stresses, while GmAOC1-expressing transgenic lines showed enhanced salinity stress tolerance [6].…”
Section: Introductionmentioning
confidence: 99%